2019
DOI: 10.1039/c9ra02461a
|View full text |Cite
|
Sign up to set email alerts
|

Lysine-based dendrimer with double arginine residues

Abstract: A new poly-l-lysine dendrimer with arginine residues was synthesized and its structure and physical–chemical properties were analyzed by NMR spectroscopy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
32
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 24 publications
(37 citation statements)
references
References 47 publications
5
32
0
Order By: Relevance
“…Computer simulation of peptide dendrimers was performed earlier by Brownian dynamics [59], molecular dynamics [60,61] methods, and by a numerical self-consistent field approach [62]. Synthesis and NMR study of some new peptide dendrimers with internally inserted amino acid spacers between each pair of branching points were also described in recent papers [63][64][65][66].…”
Section: Introductionmentioning
confidence: 99%
“…Computer simulation of peptide dendrimers was performed earlier by Brownian dynamics [59], molecular dynamics [60,61] methods, and by a numerical self-consistent field approach [62]. Synthesis and NMR study of some new peptide dendrimers with internally inserted amino acid spacers between each pair of branching points were also described in recent papers [63][64][65][66].…”
Section: Introductionmentioning
confidence: 99%
“…Both lysine and arginine are charged aliphatic amino acids with amino groups that are protonated under biological conditions, which may ensure the efficient delivery of nucleic acid into the cells and its endosomal escape. It has been shown that the insertion of Arg residues between inner Lys branching points made the dendrimer's interior more charged and thus more hydrophilic [34]. What is more, a guanidine moiety of Arg shows high affinity for phosphate groups of DNA, increasing its condensation.…”
Section: Resultsmentioning
confidence: 99%
“…In light of these results, it seemed reasonable to continue the research on the use of PLL dendrimers as carriers for other types of genetic material. Substitution of lysine residues with different amino acids may bring several benefits to PLL dendrimers considered as a system for gene delivery, changing their flexibility and distribution of charged groups, providing additional interactions with nucleic acids, and affecting cellular uptake levels [24,[33][34][35]. Both lysine and arginine are charged aliphatic amino acids with amino groups that are protonated under biological conditions, which may ensure the efficient delivery of nucleic acid into the cells and its endosomal escape.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Here, we have synthesized and deuterated a second generation lysine-based dendrimer by inserting two histidine amino acid residues into every inner segment (Figure 1). By analogy with our previous works [39,40], we have modified a dendrimer interior. The insertion of arginine or histidine amino acid residues into inner segments of lysine dendrimer could enhance its potential for drug and gene delivery (see, for instance, a recent review [19]).…”
Section: Introductionmentioning
confidence: 99%